2006
DOI: 10.1080/08860220600683581
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive Protein Is a Strong Predictor of Mortality in Hemodialysis Patients

Abstract: Serum concentration of CRP above 6.2 mg/L is a strong predictor of overall and cardiovascular mortality in patients with ESRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 30 publications
3
30
0
2
Order By: Relevance
“…These results fit with a number of studies that have shown that an elevated CRP will predict mortality from cardiovascular causes in patients with other diseases, such as diabetes or renal disease (Racki et al 2006). …”
Section: C-reactive Proteinsupporting
confidence: 74%
“…These results fit with a number of studies that have shown that an elevated CRP will predict mortality from cardiovascular causes in patients with other diseases, such as diabetes or renal disease (Racki et al 2006). …”
Section: C-reactive Proteinsupporting
confidence: 74%
“…18 Activated RAAS increased the inflammatory mediator that is an independent risk factor for CVD. [4][5][6] Activated RAAS directly increases proinflammatory gene expression and activates oxidative stress, leading to progressive inflammation of the vascular endothelium. 6 The elevated hs-CRP caused by persistent inflammation in uremic conditions has been shown to be an independent predictor of cardiovascular death in Aliskiren in hemodialysis patients Y Morishita et al HDD-CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 The elevated hs-CRP caused by persistent inflammation in uremic conditions has been shown to be an independent predictor of cardiovascular death in Aliskiren in hemodialysis patients Y Morishita et al HDD-CKD patients. 4,5 The d-ROM level represents the total level of peroxidized metabolites. d-ROM has been used to evaluate the oxidative status, and its significance as a clinical marker has been reported in various fields, including HDD-CKD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29][30][31] Poor outcomes have been associated with low albumin levels, elevated CRP or pro-inflammatory cytokine levels in ESRD patients; [32;33] collectively, elements of chronic inflammation and malnutrition appear to be among the strongest risk factors for high morbidity and mortality and low quality of life in CKD patients. [32] At present, most of the evidence implicating inflammation in adverse clinical outcomes in CKD is epidemiological, but the consistency of the studies is impressive.…”
Section: Inflammation and Outcomes In Ckdmentioning
confidence: 99%